2013
DOI: 10.1080/10962247.2012.749312
|View full text |Cite
|
Sign up to set email alerts
|

The vanishing ozone weekday/weekend effect

Abstract: A national analysis of weekday/weekend ozone (O 3 ) differences conducted using 1997-1999 data found that many urban areas experienced at least 5% higher 8-hr maximum O 3 concentrations on weekends than on weekdays even though emissions of precursors were significantly lower on weekends. This phenomenon was observed mostly in urban areas in the Northeast, Midwest, and coastal California. A similar analysis using 2008-2010 O 3 data shows that this phenomenon has mostly vanished. From 1997From -1999From to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 15 publications
3
59
1
Order By: Relevance
“…Moreover, a change in NO x -limited O 3 production regime on weekends in the three urban areas seems unlikely since this would result in lower O 3 levels on weekends, which is not observed in any of the studied urban areas (Torres-Jardon et al, 2009). Wolff et al (2013) observed similar O 3 levels during weekdays and on weekends in several urban areas in the US despite lower O 3 precursor emissions over weekends. Furthermore, the number of sites in the US that exhibited a weekend effect decreased from ca.…”
Section: Wind Occurrence At the Mmamentioning
confidence: 60%
“…Moreover, a change in NO x -limited O 3 production regime on weekends in the three urban areas seems unlikely since this would result in lower O 3 levels on weekends, which is not observed in any of the studied urban areas (Torres-Jardon et al, 2009). Wolff et al (2013) observed similar O 3 levels during weekdays and on weekends in several urban areas in the US despite lower O 3 precursor emissions over weekends. Furthermore, the number of sites in the US that exhibited a weekend effect decreased from ca.…”
Section: Wind Occurrence At the Mmamentioning
confidence: 60%
“…The resulting flux divergence recorded at our site (13 and 6% during winter and summer working-weeks compared to weekend as reference) is within the 0 and 25% deviance range from the surface fluxes for the critical zone of Damköhler number (0.1< DA <1), as demonstrated by Stella et al (2012). The chemical climate during the weekend, characterized by lower NO values, increased ratio of NO 2 /NO x leading to higher presence of O 3 , has been amply described by several authors (Fujita et al, 2003;Wolff et al, 2013). Due to a lower chemical sink during the weekends, flux measurements were less affected by flux divergence and hence, they could better represent the intrinsic O 3 deposition to the ecosystem.…”
Section: Impact Of Traffic Volumementioning
confidence: 69%
“…This result obtained here is in agreement with the findings of NOAA, 2010 which reported a potential decrease in ground level ozone of the tropical areas during 2060 to 2100 because of the higher rate of emission of ozone depleting substances (ODS) with increasing human activities. Earlier study provided evidence for this finding (Wolff et al, 2013). For example, ozone concentration is lower in Athens compared to Helsinki and Mannheim (NOAA, 2010).…”
Section: Effects Of Climate On Ozone Emission/concentrationsmentioning
confidence: 68%